Palladium‐Catalyzed Intermolecular [4+1] Spiroannulation by C(sp3)−H Activation and Naphthol Dearomatization. Issue 5 (3rd January 2019) - Tan, Bojun; Bai, Lu; Ding, Pin; Liu, Jingjing; Wang, Yaoyu; Luan, Xinjun
Abstract: A novel palladium‐catalyzed [4+1] spiroannulation was developed by using a C(sp 3 )−H activation/naphthol dearomatization approach. This bimolecular domino reaction of two aryl halides was realized through a sequence of cyclometallation‐facilitated C(sp 3 )−H activation, biaryl cross‐coupling, and naphthol dearomatization, thus rendering the rapid assembly of a new class of spirocyclic molecules in good yields with broad functional‐group tolerance. Preliminary mechanistic studies indicate that C−H cleavage is likely involved in the rate‐determining step, and a five‐membered palladacycle was identified as the key intermediate for the intermolecular coupling. Abstract : Two types of halides : A palladium‐catalyzed [4+1] spiroannulation of two types of aryl halides has been developed for the rapid construction of a new class of spirocycles. This intermolecular domino process was realized through a sequence of C(sp 3 )−H cleavage, unsymmetrical biaryl coupling, and naphthol dearomatization.